PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KAYU PADA CV. HARAPAN JAYA III KASEMEN KOTA SERANG - Ega Maulidya; Surti Zahra; Amah Suhamah (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
For the price of wood sold at CV. Harapan Jaya III is a little more expensive compared to other wood products. This study aims to determine the effect of Product Quality and Price on Wood Purchase Decisions at CV. Harapan Jaya III Kasmen Kota Serang. This type of research uses a quantitative approach with associative methods. The population in this study as many as 70 people are consumers of Wood CV. Harapan Jaya III. The sampling technique using probability sampling is a technique to provide equal opportunities for each member of the population to be selected as a member of the sample, which is as many as 70 respondents. The results showed that partially product quality had a positive effect on purchasing decisions. Then the price has a positive effect on purchasing decisions and simultaneously product quality and price affect purchasing decisions. The results of the study conclude that partially product quality affects purchasing decisions and prices affect purchasing decisions. Meanwhile, product quality and price simultaneously affect the purchase decision